2000
DOI: 10.1262/jrd.46.309
|View full text |Cite
|
Sign up to set email alerts
|

Lectin-Binding Patterns in the Testes of the Java Fruit Bat (Pteropus vampyrus) and the Japanese Lesser Horseshoe Bat (Rhinolophus cornutus).

Abstract: Abstract. Lectin binding patterns in the testes of the Java fruit bat, Pteropus vampyrus, and the Japanese lesser horseshoe bat, Rhinolophus cornutus, were investigated by light microscopy. Binding patterns were similar in both species, except for some slight differences. UEA-I, SBA, DBA and BSL-I revealed no reaction in the testes of either species. Con A and WGA gave a diffuse reaction all over the seminiferous epithelium in both species. In addition to this binding pattern, PHA-E exhibited a granular reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
2
0
4
Order By: Relevance
“…All of these bats showed active spermatogenesis according to histological analysis described below. These materials have already been used in our previous lectin-histochemical study [15].…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these bats showed active spermatogenesis according to histological analysis described below. These materials have already been used in our previous lectin-histochemical study [15].…”
Section: Animalsmentioning
confidence: 99%
“…Several studies have been reported on the testes of bats [6,10,[14][15][16][17]23]. Some of them were carried out from a morphological viewpoint.…”
mentioning
confidence: 99%
“…Bu çalışmada WGA uygulaması sonucunda hem erken, hem de geç dönem spermatidlerde güçlü ve çok güçlü reaksiyon gözlenmesine karşın, devede [9] bu hücrelerde reaksiyona rastlanmadığı belirtilmiştir. Yaban domuzu [12] erken dönem spermatidlerinde zayıf WGA reaksiyonu görülürken, java meyve yarasasında [16] çok güçlü, hamster [10] erken ve geç dönem spermatidlerinde güçlü ve dönem belirtmeksizin insan [8] spermatidlerinde de güçlü WGA reaksiyonu gözlendiği bildirilmiştir. Güvercinde de [5] spermatidlerde zayıf WGA reaksiyonuna rastlandığı belirtilmiştir.…”
Section: Tartışma Ve Sonuçunclassified
“…Erişkin at [14] Leydig hücrelerinde reaksiyona rastlamadıklarını bildirilmiştir. WGA uygulamasında deve [9] Sertoli hücrelerinde reaksiyona rastlanmadığı, yaban domuzu [12] ve hamster [10]'da orta yoğunlukta, Java meyve yarasası [16] ve geyik domuzunda [11] güçlü pozitivite belirlendiği bildirilmiştir. Bu çalışmada da at [14] ve java cüce geyiğinde [13] elde edilen bulgulara benzer şekilde Sertoli hücrelerinde zayıf reaksiyon tespit edildi.…”
Section: Tartışma Ve Sonuçunclassified
See 1 more Smart Citation